Fabrication and research of high oxygen concentration titanium implants with excellent mechanical properties and osteoconductivity - Huiwen Luo; Yapei Gao; Wendi Shi; Fei Qian; Xianzhe Shi; Xiuxia Wang; Junko Umeda; Katsuyoshi Kondoh; Yulu Wu; Jianghua Shen; Lina Niu (Materials & Design)
Titanium (Ti) and its alloys have been widely used in biomedical applications and diversity fields due to their excellent properties. In this study, high oxygen concentration titanium (HOC-Ti) was developed to enhance the mechanical properties and osseointegration capacity of commercially pure titanium (CP-Ti) for dental implants. By increasing the internal oxygen content, not only the grain size was decreased, but the strength and toughness of HOC-Ti were also outstanding improved in this work. Among the tested samples, HOC-Ti with an oxygen content of 0.52 wt% exhibited well-balanced set of mechanical characteristics, making it the potentially suitable candidate for dental implant applications. In addition, the results of micro/nanocomposite structures formed on the HOC-Ti surface through anodic oxidation effectively promoted the osteogenic differentiation of osteoblasts, guided macrophage polarization toward the M2 phenotype, and inhibited osteoclast activity. And the vivo experiments further demonstrated superior osseointegration of HOC-Ti implants. RNA sequencing analysis suggested that HOC-Ti may influence osteoblast adhesion and enhance osteogenic differentiation by activating the MAPK pathway, while concurrently inducing endoplasmic reticulum stress responses and suppressing osteoclast function of osteocyte. In summary, HOC-Ti represents a promising new option for dental implants and provides a solid foundation for future clinical applications.